2021
DOI: 10.1001/jamaoncol.2021.2159
|View full text |Cite
|
Sign up to set email alerts
|

Difference in SARS-CoV-2 Antibody Status Between Patients With Cancer and Health Care Workers During the COVID-19 Pandemic in Japan

Abstract: IMPORTANCE Patients with cancer and health care workers (HCWs) are at high risk of SARS-CoV-2 infection. Assessing the antibody status of patients with cancer and HCWs can help understand the spread of COVID-19 in cancer care. OBJECTIVE To evaluate serum SARS-CoV-2 antibody status in patients with cancer and HCWs during the COVID-19 pandemic in Japan. DESIGN, SETTING, AND PARTICIPANTS Participants were enrolled for this prospective cross-sectional study between August 3 and October 30, 2020, from 2 comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
52
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 38 publications
6
52
0
2
Order By: Relevance
“…Overall, the subgroup analysis demonstrated that the adverse impacts of chemotherapy mainly occurred in patients with haematologic malignancies. However, for patients with solid tumors, immunotherapy could lead to life-threatening outcomes, especially when administered within 50 d. Both chemotherapy and immunotherapy were reported to affect SARS-CoV-2 antibody levels in patients and could influence the immune response to SARS-CoV-2 (Yazaki et al, 2021). In fact, some previous studies even indicated that chemotherapy increased the risk of poor outcomes (Grivas et al, 2021;Sharafeldin et al, 2021), especially in patients with haematologic malignancies (Lee et al, 2020b), which is in agreement with our results.…”
supporting
confidence: 91%
“…Overall, the subgroup analysis demonstrated that the adverse impacts of chemotherapy mainly occurred in patients with haematologic malignancies. However, for patients with solid tumors, immunotherapy could lead to life-threatening outcomes, especially when administered within 50 d. Both chemotherapy and immunotherapy were reported to affect SARS-CoV-2 antibody levels in patients and could influence the immune response to SARS-CoV-2 (Yazaki et al, 2021). In fact, some previous studies even indicated that chemotherapy increased the risk of poor outcomes (Grivas et al, 2021;Sharafeldin et al, 2021), especially in patients with haematologic malignancies (Lee et al, 2020b), which is in agreement with our results.…”
supporting
confidence: 91%
“…Moreover, this analysis confirmed the results in the chemotherapy and non-chemotherapy treated sub-groups. Likewise, two recently published articles described a reduced immune response to SARS-CoV-2 in patients with solid malignant neoplasms undergoing active cancer therapy [19,26]. Monin et al have lately reported better immunogenicity after two versus one vaccine dose in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable analysis showed that the only variable statistically significantly associated with lower IgG titer was treatment with chemotherapy plus immunotherapy ( 22 ). Although the evidence are lacking, it seems comorbid cancer and treatment with systemic therapy, including chemotherapy, may influence the immune response to SARS-CoV-2 and potentially COVID-19 vaccination ( 23 ).…”
Section: Discussionmentioning
confidence: 99%